KAJIAN EUTHANASIA PASIF DALAM PERSPEKTIF HUKUM PIDANA INDONESIA - Judika Atma Togi Manik; Mahmud Mulyadi; Suhaidi Suhaidi; Muhammad Ekaputra (Universitas Sumatera Utara, 2017)
ABSTRACT Euthanasia is a debate among lawyers, medical experts and theologians in which euthanasia is an act of facilitating the death of a person deliberately without feeling the pain of affection with the aim of alleviating the suffering of the sick, until now there has been no clarity about the punishment that really exist In the criminal law in Indonesia but there are articles that can be used as guidance in determining the law for passive euthanasia actors namely articles 304, 306, 338, 344 and 359 of the Criminal Code and the practice of passive euthanasia is very contrary to human rights in Indonesia for violating the right of life Patients who want to get a cure from the disease even though the disease is medically can not be cured. Based on the results of this study it can be concluded that passive euthanasia in criminal law in Indonesia can be categorized as crime under article 304, 306, 338, 344, and 359 of the Criminal Code. Who can be sentenced to 7 years and 12 years the longest. Although in it does not directly refer to passive euthanasia, but at least that article can be used as a reference or guidance on the enactment of criminal sanctions for passive euthanasia actors. Key words : Euthanasia, Criminal Law